Sistem Pendukung Keputusan Menentukan Tingkat Resiko Penjualan Online Dengan Menggunakan Metode TOPSIS - Yosapat Sembiring; Paska Marto Hasugian (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
At this time many people have started selling online. Even though only with makeshift items to make online sales, not a few people have succeeded in making these online sales. The TOPSIS method is one of the multicriteria decision-making methods, this method is one that is widely used to complete practical decision making. The more factors that must be considered in the decision making process, the more difficult it will be to make a decision on an issue. identification of research problems is the application of the DSS in determining the level of risk of online sales. This system was built using the PHP programming language with data management using the MySQL database. Rank results 1. Furniture = 0.8062 2.Electronics = 0.5810 3. Fashion = 0.1230